Identification of a panel of cytokines in neonates with hypoxic ischemic encephalopathy treated with hypothermia. (November 2018) - Perrone, Serafina; Weiss, Michael D.; Proietti, Fabrizio; Rossignol, Candace; Cornacchione, Sara; Bazzini, Francesco; Calderisi, Marco; Buonocore, Giuseppe; Longini, Mariangela
Abstract: Purpose: Inflammation is a crucial but understudied mechanism of neuronal injury after hypoxia-ischemia. The aim was to identify a panel of cytokines involved in brain injury in neonates with hypoxic ischemic encephalopathy (HIE). Methods: Ten newborns with HIE undergoing to therapeutic hypothermia (TH, HIE Group) and 8 healthy newborns (CTRL Group) were enrolled. For the HIE group, 5 samples were collected: between 0 and 6 h of life (time 1), 12 h (time 2), 24 h (time 3), 48 h (time 4) and 96 h of life (time 5). For the CTRL group, one sample was collected. A panel of 48 inflammatory cytokines was determined in all samples. Data were analyzed using multivariate statistical analysis (Principal component analysis, PCA) Results: 17 cytokines, among 48 analyzed, were found to be significantly different, initially, between the CTRL and HIE groups: 12 with reported pro-inflammatory effects and 5 with reported anti-inflammatory effects. In the HIE group cytokines showed a decreasing trend during the TH and at the end of treatment comparable to the CTRL group. IL-18 did demonstrate a slight increase at time 3 during HT but decreased steadily at sampling times, 4 and 5. Conclusions: Our data demonstrates that many pathways of the inflammatory cascade are activated following hypoxic-ischemic injury. This information will increase our understanding of changes in cytokines over time in neonates with HIE undergoing TH.